Health-related quality of life among adolescents: A comparison between subjects at ultra-high risk for psychosis and healthy controls - Nitka, Freya; Kalmar, Julia; Parzer, Peter; Resch, Franz; Henze, Romy (Psychiatry research, 2016)
At risk status for psychosis has been robustly associated with decreased health-related quality of life (HRQoL) among adults. However, this relationship has not been examined in adolescents with ultra-high risk (UHR) for psychosis in comparison to healthy controls. Twenty-seven subjects with UHR and thirty healthy controls (14-18 years of age) were recruited in a multiphase screening and accessed with a HRQoL scale of KIDSCREEN-27. Comparisons indicated that subjects with UHR had poorer mean scores at a statistically significant level in the following scales: physical well-being, psychological well-being and school environment. In a logistic regression analysis, lower scores in the scale school environment explained at risk status for psychosis. Adolescents with UHR show significantly poorer HRQoL scores than healthy peers, identified predominantly by the evaluation of the school environment. These results might be interpreted as a self-perception of early mental and social functioning impairments, which seem to be recognized initially based on school demands. Considering these findings, institutes of education should be a good starting point to promote the awareness of the psychosis-risk state.